Functional Outcome in Paraplegic Patients from Spinal Cord Injury (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Background: Patients with Spinal Cord Injuries (SCI) are confronted with motor and sensory deficits as well as bladder, bowel and sexual dysfunction, which lead to a fundamental change of life. Because of the extensive medical, emotional and social consequences of the SCI, multidisciplinary management is essential. This study focuses on the functional outcome after a spinal cord injury.Methods: This was an observational study done during a period of 6 months from July 2007 to December 2007 among paraplegic spinal cord injured patients, admitted in the Neurosurgery Department and attended in the Department Physical Medicine and Rehabilitation, Chittagong Medical College, Chittagong. A total of 50 patients were selected for the study. Sampling technique was purposive and different scores and followup findings were collected and analyzed by Statistical Package for Social Science (SPSS-15) P value < 0.05 was considered as significant.Results: Mean age of study population was 32.7 years with all patients were between 18 to 55 years age range. Male and female ratio was 9:1. Maximum respondents were day labourer 36.0%, followed by 34.0% other different types of occupation, 10.0% business man, 8.0% service holder, 8.0% housewife and 4.0% student. Fall from height was the major cause of spinal cord injury of the present study group followed by Road Traffic Accident (RTA). Out of all patients 50.0% had urinary incontinence, 44.0% hadbowel incontinence, 46.0% had spasticity, 34.0% had hypotension and 4.0% had bed sore. At pretreatment stage mean (±SD) FIM score of the patients was 92.5 and discharge 107.32. (p